Projekt etyki naukowej w System der Ethik Wilhelma Diltheya (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The article presents the conclusions drawn from the analysis of Wilhelm Dilthey’s System der Ethik. It takes into account mainly epistemological and methodological problems, which are important due to the goals set by Dilthey’s ethics, i.e. the formulation of a scientific theory that will contain universally valid judgments. Basic questions that the author of the article tries to answer are: 1) What does Dilthey mean by “scientific” in the postulative sense? 2) How does he actually implement his “scientific” ethics? 3) What are the theoretical effects of this implementation? 4) How to evaluate these effects and, above all, does Dilthey realise ethics as a science? Can Dilthey’s project of ethics be relevant today and if so, in what aspects?